Relationship between inclusion of internship, diversification of physical education program and sport development in nigeria (2012)
The gap between developed and underdeveloped countries has become so wide that the latter have lost any hope of closing it in terms of either sport performance or organization of big sports events. Problems of sport development in a developing and emerging nation like Nigeria has been linked to lack of proper manpower training. Physical education and sport management courses for long offer a good platform for manpower training of sport managers, unfortunately the pedagogical nature of physical education has dwarfed the scope of the course. The decline status of physical education is as a result of low level of awareness among Nigerians of the merits of physical education. This lack of knowledge has led to decline in the enrolment in physical education and recreation classes particularly in tertiary institutions. Comparison of some Nigerian universities physical education programmes with those in the developed countries reveals a great disparity. While the developed countries have diversified their physical education curriculum to pave way for the emergence of several sport related disciplines, in order to keep pace with the high level of sport development, Nigeria still sticks with curriculum cum programmes that was developed in the 1960s. Perhaps taking a global look on this issue by developing attractive and relevant sport programmes from the current physical education/human kinetics and inclusion of internship in addition to teaching practice will assist in developing Nigerian Sport to enviable height. Descriptive survey research design was used for this study. The sample consisted of 2003 participants selected from among physical education students (graduate and undergraduate), lecturers and sport practitioners through purposive and incidental sampling techniques. Simple random sampling technique was used to select 4 national sport commission development zones and 18 state sport councils spread across the selected zones. While stratified random sampling technique was used to group the 24 universities offering physical education programme into the 4 selected zones, simple random sampling technique was used to select at least 50% of the universities offering Physical Education programme in each of the selected zones. The instruments used for data collection were sport curriculum diversification scale (r=0.81), and sport development scale (r=0.79). Two research hypotheses were formulated and tested at 0.05 alpha level. Data collected were analyzed using inferential statistics of multiple regression, and descriptive statistics of mean and standard deviation. The findings reveal that inclusion of internship and improved subject status of physical education are significant to sport development; Internship (6=.055, P (.015) < 0.05), improve subject status (6=.099, P (.000) < 0.05. The result shows that the two predictor variables were independently significant. The study also revealed that development of new sport disciplines will contribute to sport development and improved status of physical education in Nigeria. It is recommended that to improve sport development in Nigeria there is need for development of new sport disciplines at the undergraduate level to attract more brilliant students into the field of sport management and to ensure provision of adequate qualify manpower for the nation's sport sector. It was also recommended that internship should be included in tandem with teaching practice exercise in the physical education curriculum